Meningkatkan Literasi Data Melalui Kecerdasan Buatan (AI): Sebuah Pendekatan Toastmaster International - Rita Hartati; Tindaon, Marta Friska (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2025)
Data Literacy is the essential competency in this digital era. However, there is a lot of college students have difficulty in comprehending and delivering the information data-driven information effectively. This study aims to explore the potential of Artificial Intelligence (AI) in enhancing data literacy through implementation of International Toastmaster project which has been proven effective in developing speaking and leadership skill. Mix method is conducted in this study which involve 30 english literature students of State University of Medan who have follow International Toastamaster program. This study evaluates the influence of Artificial Intelligence (AI) which is intergrated in 10 International Toastmaster project for developing data literacy within the framework of a structured Toastmasters program. The data was collected through questionaires, interviews and survey for evaluating data literacy level of the students. The finding of this study shows that the integration of Artificial Intelligence (AI) in 10 International Toastmaster project can significantly improve students’ ability in analyzing, interpreting and presenting data findings. The finding indicates that the integration can increase essential speaking skills to face challenges in an increasingly data-dependent era.